Facile fabrication of TiO2@TiO2 transparent free‐standing film for photocatalysis. (16th January 2019) - Zhang, Shanmei; Hu, Yue; Hu, Luyang; Zhang, Yumin; Zhou, Yufeng; Li, Benxia
Abstract : A transparent titanium dioxide (TiO2 )@TiO2 film with free‐standing structure was synthesised by employing a cellulose paper as the template. By one‐step hydrothermal method and subsequent thermal annealing, the fibre of cellulose paper was changed into porous TiO2 core layer. The flower‐like micro/nanostructure TiO2 particle layer was intimately distributed on the porous TiO2 core layer. The average diameter of the TiO2 @TiO2 fibre for the film was 11 μm. The size of spherical granular TiO2 on the fibre surface was around 330 ± 130 nm. It was noted that the microtopography of fibre surface could be adjusted by tuning the hydrothermal temperature. The scanning electron microscopy and N2 adsorption–desorption measurement results indicated that the prepared film possessed a large mass of mesopores and macropores. On the basis of the special microstructure, the TiO2 @TiO2 film exhibited high photocatalytic activity for methylene blue under ultraviolet irradiation. This work might provide a new insight for preparation of transparent photocatalytic film toward water purification.